2007
DOI: 10.1179/174329007x161982
|View full text |Cite
|
Sign up to set email alerts
|

Use of PM Fe–Cu–SiC composites as bonding matrix for diamond tools

Abstract: The use of the system Fe- (5,10,15,20)%Cu with the addition of 1% weight of silicon carbide (SiC) as bonding matrix for diamond tools was investigated in the present work. The diamond metallic composites were manufactured via conventional powder metallurgy and sintered at 1050 and 1150uC. Evaluation of the composites included the measurement of the level of shrinkage/ swelling, Brinell hardness and wear resistance. Microstructure was investigated via scanning electron microscopy (SEM). The results show that te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The progressing process of oxidation of the powders could also contribute to the reduction of the sinter density. The material is characterized by a high coefficient of thermal expansion, which ensures good retention of diamond particles in the metallic-diamond composite [1,[8][9][10][27][28][29][30]. The influence of the mechanical parameters and thermal expansion of the matrix on the retention of diamond particles is currently intensively studied, both experimentally and through computer and mathematical modeling [11][12][13][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The progressing process of oxidation of the powders could also contribute to the reduction of the sinter density. The material is characterized by a high coefficient of thermal expansion, which ensures good retention of diamond particles in the metallic-diamond composite [1,[8][9][10][27][28][29][30]. The influence of the mechanical parameters and thermal expansion of the matrix on the retention of diamond particles is currently intensively studied, both experimentally and through computer and mathematical modeling [11][12][13][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that the combined effect of high copper content and SiC, alloy composition Fe + 20 wt%Cu + 1 wt%SiC sintered at 1 150°C offer abrasion wear resistance 2 times higher than the other compositions. 29) Yu-Zan Hsieh et al, revealed, effect of coating of diamond grit with active element such as Titanium in iron-based matrix. This form a transitional layer between diamond grit and iron matrix and prevent the degradation of diamond.…”
Section: Iron Powder In Diamond Cutting Toolsmentioning
confidence: 99%
“…Diamond tools are widely used for cutting, grinding, sawing, drilling, and polishing hard materials, such as stone, concrete, cemented carbides, optical glass, advanced ceramics, and other difficult-to-process materials [1][2][3]. This is due to diamond's unique physicochemical characteristics, namely its extreme hardness and high strength, as well as its good abrasion resistance and low thermal expansion [4].…”
Section: Introductionmentioning
confidence: 99%